A Hypothetical Bottleneck in the Plant Microbiome - Newcombe, George (Front Microbiol, 2018)
The plant microbiome may be bottlenecked at the level of endophytes of individual seeds. Strong defense of developing seeds is predicted by optimal defense theory, and we have experimentally demonstrated exclusionary interactions among endophytic microbes infecting individual seeds of Centaurea stoebe. Having found a single, PDA-culturable microbe per seed or none in an exploratory study with Centaurea stoebe, we completed a more extensive survey of an additional 98 plant species representing 39 families. We again found that individual, surface-sterilized seeds of all species hosted only one PDA-culturable bacterial or fungal endophyte per seed, or none. PDA-unculturables were not determined but we expect them to also be bottlenecked in individual seeds, as they too should be governed by exclusionary interactions. If the bottleneck were confirmed with high-throughput sequencing of individual seeds then it would make sense to further investigate the Primary Symbiont Hypothesis (PSH). This includes the prediction that primary symbionts (i.e., the winners of the exclusionary battles among seed endophytes) have strong effects on seedlings depending on symbiont identity.